Role of chalcogen atoms in in situ exfoliation of large-area 2D semiconducting transition metal dichalcogenides - Dan, Zhiying; Sarmasti Emami, Ronak; Feraco, Giovanna; Vavali, Melina; Gerlach, Dominic; Sarott, Martin F; Zhu, Yindi; Rudolf, Petra; Grubišić-Čabo, Antonija (Frontiers in Nanotechnology, 2025)
Two-dimensional (2D) transition metal dichalcogenides have emerged as a promising platform for next-generation optoelectronic and spintronic devices. Mechanical exfoliation using adhesive tape remains the dominant method for preparing 2D materials of highest quality, including transition metal dichalcogenides, but always results in small-sized flakes. This limitation poses a significant challenge for investigations and applications where large scale flakes are needed. To overcome these constraints, we explored the preparation of 2D WS2 and WSe2 using a recently developed kinetic in situ single-layer synthesis method (KISS). In particular, we focused on the influence of different substrates, Au and Ag, and chalcogen atoms, S and Se, on the yield and quality of the 2D films. The crystallinity and spatial morphology of the 2D films were characterized using optical microscopy and atomic force microscopy, providing a comprehensive assessment of exfoliation quality. Low-energy electron diffraction verified that there is no preferential orientation between the 2D film and the substrate, while optical microscopy revealed that WSe2 consistently outperformed WS2 in producing large monolayers, regardless of the substrate used. Finally, X-ray diffraction and X-ray photoelectron spectroscopy demonstrate that no covalent bonds are formed between the 2D material and the underlying substrate. These results identify KISS method as a non-destructive method for a more scalable approach of high-quality 2D transition metal dichalcogenides.